Free and conjugated estrogens detections in drainage tiles and wells beneath fields receiving swine manure slurry. (January 2020) - Casey, Francis X.M.; Hakk, Heldur; DeSutter, Thomas M.
Abstract: Although livestock manure, such as from swine ( Sus scrofa domestica ), have high capacity to introduce endocrine-disrupting free estrogens into the environment, the frequency of estrogen detections from reconnaissance studies suggest that these compounds are ubiquitous in the environment, perhaps resulting from historic manure inputs (e.g. cattle grazing residues, undocumented historic manure applications) or uncontrolled natural sources. Compared to free estrogens, conjugates of estrogens are innocuous but have greater mobility in the environment. Estrogen conjugates can also hydrolyze to re-form the potent free estrogens. The objective of this study was to identify the transport of free and conjugated estrogens to subsurface tile drains and groundwater beneath fields treated with swine manure slurry. Three field treatments were established, two receiving swine lagoon manure slurry and one with none. Manure slurry was injected into soils at a shallow depth (∼8 cm) and water samples from tile drains and shallow wells were sampled periodically for three years. Glucuronide and sulfate conjugates of 17β-estradiol (E2) and estrone (E1) were the only estrogen compounds detected in the tile drains (total detects = 31; 5% detection frequency; conc. range = 3.9–23.1 ng L −1 ), indicating the important role conjugates played in the mobility of estrogens. Free estrogens and estrogen conjugates were more frequently detected in the wells compared to the tile drains (total detects = 70; 11% detection frequency; conc. range = 4.0–1.6 × 10 3 ng L −1 ). No correlations were found between estrogen compound detections and dissolved or colloidal organic carbon (OC) fractions or other water quality parameters. Estrogenic compounds were detected beneath both manure treated and non-treated plots; furthermore, the total potential estrogenic equivalents (i.e. estrogenicity of hydrolyzed conjugates + free estrogens) were similar between treated and non-treated plots. Graphical abstract: Image 1 Highlights: Conjugates can facilitate estrogen mobility in the environment. Historic/wildlife sources of estrogens are contribute estrogenicity similar to de novo livestock manures. o - Greater estrogen mobility can increase estrogen concentrations in receiving water systems.